Seroprevalence and risk assessment of viral hepatitis E infection in a group of exposed persons from Republic of Moldova - Sajin, Octavian; Spînu, Constantin; Pînzaru, Iurie; Isac, Maria; Spînu, Igor; Guțu, Veaceslav; Paraschiv, Angela; Suveică, Luminița (The Journal of Infection in Developing Countries, 2019)
Introduction: Viral hepatitis E is considered to be an important issue for public health in developing countries. The aim of the present study is to evaluate morbidity and risk factors in occupationally exposed groups such as people working on sausage production. Methodology: Seroprevalence of HEV (hepatitis E virus) and risk factors to infection were determined in a cross-sectional study of two groups of populations: people working on sausage production (n = 70) and persons without occupational exposure (people working in the textile industry n = 70) in Moldova, a country without reported cases of hepatitis E. Results: The seroprevalence of HEV was 14.3% (CI 95%, 13.1-15.5%) in the group of exposed, compared with no cases in the non-exposed group that indicates on no previous infectious contact with hepatitis E virus. Conclusions: The increased seroprevalence of HEV among persons with occupational exposure to swine meat suggest animal-to-human transmission of this infection.